G452(P) Not just a pain in the neck? an unusual case of an infant presenting with a stiff neck, diagnosed with septic arthritis of the atlantoaxial joint and osteomyelitis of the odontoid peg. (27th April 2015) - Murray, S; Coleman, C; Russell-Taylor, M
Abstract : Primary acute osteomyelitis of the first and second vertebrae is extremely rare in the paediatric population, and there is no literature documenting septic arthritis of the atlantoaxial joint secondary to odontoid osteomyelitis. We present the case of a 10–month–old, well child presenting with a stiff neck, with no clinical features suggestive of infection. Blood tests revealed a mildly elevated white cell count and CRP, with a normal ESR. Notably his alkaline phosphatase was markedly elevated. A lateral cervical spine X–ray excluded bony pathology, but revealed pre–cervical soft tissue swelling. MRI showed extensive signal change in the odontoid peg, along with enhancement and fluid distension of the joint capsule – appearances in keeping with a diagnosis of septic arthritis of the atlanto–axial joint and osteomyelitis of the odontoid peg. The patient was commenced on once–daily intravenous antibiotics for six weeks, before switching to oral therapy for a total of three months. He responded well to treatment and recovered a full range of neck movements. Repeat imaging demonstrated resolution of inflammatory changes, and he was discharged from follow–up. A high index of suspicion is required for the diagnosis of osteomyelitis, as it has variable presentation and initial investigations may be misleading. This case indicates that nuclear imaging should be done as a matter of urgency in a child who has no appreciable active or passive neck movement to rule out bony pathology, and that although a rare cause of stiff neck in children, odontoid peg osteomyelitis should be considered as a differential diagnosis even in a child who does not look septic. This case also illustrates that odontoid peg osteomyelitis may subsequently lead to septic arthritis of the atlantoaxial joint, which has not been previously described in the literature.